The Dynamics of Implementing Sharia Accounting Standards in Sharia Financial Institutions - Qimyatussa’adah, Qimyatussa’adah; Ramadhani, Raihand (International Journal of Magistravitae Management, 2024)
This study aims to explore the dynamics of implementing Sharia Accounting Standards (SAS) in Indonesian sharia-compliant financial institutions. A systematic literature review was conducted to examine publications related to SAS. The findings reveal that several factors influence adoption, including technical aspects such as differences in practitioners' understanding and expertise in Sharia accounting standards. Moreover, governance issues emerge due to diverse models of Sharia compliance governance across countries and disparities in the growth of the Islamic finance sector. Additionally, challenges related to adherence to the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standards, conflicts between multiple accounting frameworks, and the need for a unified accounting structure pose significant obstacles to the implementation of Sharia-based financial reporting standards in Islamic financial institutions. The study also identifies variations in SAS application across Islamic financial organizations. While some institutions demonstrate high compliance and seamless integration, others struggle to adopt and implement the standards. Challenges such as a lack of competent human resources, differences in standard interpretation, and the need for accounting system adjustments further complicate the implementation process. The study concludes that despite the various challenges in implementing Sharia Accounting Standards, strong regulatory support, enhanced education and training initiatives, and collaboration among Sharia financial institutions can mitigate these issues and improve the effectiveness of Sharia-compliant financial reporting in Indonesia.